Influence of a remelt scan strategy on the microstructure and fatigue behaviour of additively manufactured biomedical Ti65Ta efficiently assessed using small scale specimens. (September 2022) - Brodie, Erin G.; Richter, Julia; Wegener, Thomas; Molotnikov, Andrey; Niendorf, Thomas
Highlights: Ti65Ta additively manufactured as new potential biomedical alloy. Small specimens used for mechanical testing to represent small implants. Remelt scan strategy decreased remaining partially melted Ta particles. Remelt scan strategy increased material strength and low cycle fatigue life. Abstract: Due to its high cost and demanding characteristics, Tantalum requires unique processing techniques and is restricted to small parts. In the present work, Ti65Ta was additively manufactured as a new potential material for small biomedical implants. Assessment of the effects of a remelt scanning strategy was solely accomplished by testing of small mechanical specimens. Yield strength was achieved superior to either L-PBF pure Ti or Ta and low-cycle fatigue behaviour was similar to that of L-PBF Ti-6Al-4 V. The Ti65Ta alloy is a good candidate for a new gold standard alloy for small bone interfacing implants.